Association between PCV13 pneumococcal vaccination and risk of hospital admissions due to pneumonia or sepsis among patients with haematological malignancies: a single-centre retrospective cohort study in Israel. Issue 4 (15th April 2022) - Draliuk, Regina; Shadmi, Efrat; Preis, Meir; Dagan, Efrat
Abstract : Objectives: Patients with haematological malignancies receiving immunosuppressive therapy are at highest risk of invasive pneumococcal disease. Our goal was to investigate whether vaccination of haematological patients with pneumococcal 13-valent conjugated vaccine (PCV13) prior to therapy initiation is associated with decreased hospital admissions due to pneumonia or sepsis within 12 months. Design and setting: A longitudinal retrospective cohort study was conducted at the haematology unit of Carmel Medical Center, Israel. Participants: Information on adult patients (>18 years) who were diagnosed between 1 January 2009 and 30 December 2019 with haematological malignancies and received immunosuppressive therapy was retrieved from the electronic health records. Patients with haematological malignancies who received the PCV13 vaccination during or after initiation of the immunosuppressive therapy were excluded from the study. Outcome measures: A multivariate logistic regression model was performed to determine whether PCV13 vaccination is associated with fewer hospital admissions due to pneumonia or sepsis. Results: The cohort included 616 patients, of which 418 (67%) patients were not vaccinated and 198 (33%) were vaccinated. Within 12 months, 15.1% (n=63) of non-vaccinated patients compared with only 7.1% (n=14) of the vaccinated patients were hospitalised due to pneumonia or sepsis. The logistic regression analysis demonstrated that receiving PCV13 vaccination is associated with 45% (OR=0.45, 95% CI: 0.246 to 0.839, p=0.012) reduced odds of being hospitalised due to pneumonia or sepsis in patients with haematological malignancies receiving immunosuppressive therapy. Conclusion: This is the first observational study to demonstrate the association between PCV13 vaccination and hospital admissions in patients with haematological malignancies receiving immunosuppressive therapy. Patients receiving PCV13 vaccination before immunosuppressive therapy initiation had significantly reduced odds of hospitalisation due to pneumonia or sepsis compared with non-PCV13-vaccinated patients.